2018
DOI: 10.1186/s12887-018-1171-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific effects of perinatal dioxin exposure on eating behavior in 3-year-old Vietnamese children

Abstract: BackgroundWe previously reported that perinatal dioxin exposure increased autistic traits in children living in dioxin-contaminated areas of Vietnam. In the present study, we investigated the impact of dioxin exposure on children’s eating behavior, which is often altered in those with developmental disorders.MethodsA total of 185 mother-and-child pairs previously enrolled in a birth cohort in dioxin-contaminated areas participated in this survey, conducted when the children reached 3 years of age. Perinatal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Wang et al 2019;Ames et al 2019), and subsequently impact adult health. There are also interesting sex-specific effects reported in these populations (Nishijo et al 2012;Nguyen et al 2018;Tai et al 2016;Pham et al 2020;Z. Wang et al 2019;Ames et al 2019), further emphasizing the need for sex-stratified data in the epidemiology literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al 2019;Ames et al 2019), and subsequently impact adult health. There are also interesting sex-specific effects reported in these populations (Nishijo et al 2012;Nguyen et al 2018;Tai et al 2016;Pham et al 2020;Z. Wang et al 2019;Ames et al 2019), further emphasizing the need for sex-stratified data in the epidemiology literature.…”
Section: Discussionmentioning
confidence: 99%
“…Age of exposure is an important covariate that we could not control for in our metaanalysis, but we limited our inclusion criteria to studies on adult populations to minimize variability. Childhood exposure to dioxins and DL-PCBs is associated with myriad complications that can present at birth (Tawara et al 2009;Nghiem et al 2019) and childhood (Nguyen et al 2018;Nishijo et al 2012;Tai et al 2016;Tran et al 2016;Pham et al 2020;Z. Wang et al 2019;Ames et al 2019), and subsequently impact adult health.…”
Section: Discussionmentioning
confidence: 99%
“…These districts are located within 10 km of the former Da Nang airbase and are hot spots of dioxin contamination originating from herbicide spraying in Vietnam. The subjects were children from the Da Nang birth cohort, including 238 mother and infant pairs (158 pairs in Thanh Khe and 80 pairs in Son Tra) recruited in the period 2008–2009; we reported the impacts of dioxins on their growth and neurodevelopment in follow-up studies from 1 month later to the present time [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Perinatal dioxin exposure originating from the airbase can influence specific developmental aspects, as shown by the ASD-type difficulties in social interactions as well as poor general neurodevelopment, including language and motor skills, in children from the Da Nang birth cohort recruited in the period 2008–2009 in Da Nang city in Vietnam [ 10 , 11 , 12 , 13 , 14 ]. In these children, particularly in girls, at 3 years of age perinatal dioxin exposure influenced their eating behavior, such as enjoyment of foods, suggesting that the effects of dioxins on emotional development may lead to emaciation/obesity in the future [ 15 ]. We also investigated their neurodevelopment at 5 years of age and reported that lower planning ability and poor coordination and motor skills were associated with perinatal dioxin exposure [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Các điểm số thành phần trong bộ câu hỏi CEBQ đã được chứng minh phản ánh tốt và độ tin cậy cao ở trẻ từ 1-13 tuổi ở nhiều nước trên thế giới như Thuỵ Điển [16], Chile [23], Canada [24], Trung Quốc [25]. Tại nước ta, việc áp dụng bộ câu hỏi CEBQ để đánh giá đặc điểm ăn uống của trẻ còn chưa phổ biến, mới có công bố mới đây của Nguyễn Thị Nguyệt Anh (2018) thực hiện trên trẻ 3 tuổi bị nhiễm chất độc Dioxin [26] là sử dụng bộ câu hỏi này. Nghiên cứu của chúng tôi cho thấy việc tăng 1 điểm số ở chỉ số EF (thích ăn) và DD (thích nước ngọt) làm giảm nguy cơ SDD ở trẻ với OR là 0,69 và 0,82, tương ứng (P<0,05).…”
Section: ảNh Hưởng Của đặC đIểm ăN Uống đếN Tình Trạng Dinh Dưỡng Củaunclassified